Cytogenomic analysis unveils mixed molecular evolution and recurrent chromosomal rearrangements shaping the multigene families on Schistocerca grasshopper genomes - Martí, Emiliano [UNESP]; Milani, Diogo [UNESP]; Bardella, Vanessa B. [UNESP]; Albuquerque, Lucas [UNESP]; Song, Hojun; Palacios-Gimenez, Octavio M.; Cabral-de-Mello, Diogo C. [UNESP] (Oxford University Press (OUP), 2021)
Multigene families are essential components of eukaryotic genomes and play key roles either structurally and functionally. Their modes of evolution remain elusive even in the era of genomics, because multiple multigene family sequences coexist in genomes, particularly in large repetitive genomes. Here, we investigate how the multigene families 18S rDNA, U2 snDNA, and H3 histone evolved in 10 species of Schistocerca grasshoppers with very large and repeat-enriched genomes. Using sequenced genomes and fluorescence in situ hybridization mapping, we find substantial differences between species, including the number of chromosomal clusters, changes in sequence abundance and nucleotide composition, pseudogenization, and association with transposable elements (TEs). The intragenomic analysis of Schistocerca gregaria using long-read sequencing and genome assembly unveils conservation for H3 histone and recurrent pseudogenization for 18S rDNA and U2 snDNA, likely promoted by association with TEs and sequence truncation. Remarkably, TEs were frequently associated with truncated copies, were also among the most abundant in the genome, and revealed signatures of recent activity. Our findings suggest a combined effect of concerted and birth-and-death models driving the evolution of multigene families in Schistocerca over the last 8 million years, and the occurrence of intra- and interchromosomal rearrangements shaping their chromosomal distribution. Despite the conserved karyotype in Schistocerca, our analysis highlights the extensive reorganization of repetitive DNAs in Schistocerca, contributing to the advance of comparative genomics for this important grasshopper genus.
Keywords: Birth-and-death; concerted evolution; FISH; large genomes; repetitive DNAs; transposable elements